Design and Energy-Saving Analysis of a New LNG Vaporizer Based on Mg-Based Hydrogen Storage Metal - Wenke Yuan; Zixuan Yin; Yan Su; Zhangyu Liu; Leyi Bao; Jinyu An (Energies)
In order to save the large amount of energy consumption associated with traditional water-bath LNG vaporizer, this paper proposes a novel design for a liquefied natural gas (LNG) vaporizer by comprehensively applying the exothermic property of hydrogen storage metals and the high efficiency of solar energy storage devices. In this paper, the working theory of the proposed LNG vaporizer is first addressed; then, a system featuring a new LNG vaporizer with 1312 mm diameter and 4000 mm length is designed, and its feasibility is demonstrated through technical and economic analysis. After comparison, Mg2Ni has higher economic benefits as a hydrogen storage metal than Mg. When Mg2Ni is used as the hydrogen storage metal, the daily power consumption for vaporizing 1000 m3 of LNG at night during winter is just 89.78 kW·h, with an energy efficiency of about 50%. Combined with solar energy storage devices, for a northern city in China (about 40° N), the savings in electricity costs could be about $2200 per year.